The Role of Maternal Acceptance in Mediating Child Outcomes Among Substance Using Women Experiencing Intimate Partner Violence - Cully, Laura (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is prevalent in the United States, and many women who experience IPV have children in their care. Substance use is common among this population and affects parenting behaviors such as maternal acceptance and child outcomes. Maternal experience of IPV affects a mother’s ability to parent and interact with her child. Little is known about the combined influence of both maternal substance use and IPV on parenting behaviors and child problem behaviors. The current study examined differences in maternal acceptance and child internalizing and externalizing behaviors among mothers who reported experiencing IPV to mothers who never reported experiencing IPV. Results showed that mothers with a history of IPV reported lower rates of maternal acceptance and higher rates of child problem behaviors compared with those with no history of IPV. In addition, frequency of substance use moderated this relationship. This is the first study, to date, to examine the relationship between maternal acceptance and child problem behaviors among substance using mothers with a history of IPV and is a first step to understanding the parenting practices of this population.